Acute Aortic Valve Rupture from Infective Endocarditis after Transrectal Prostate Biopsy: A Call to Revise the AHA Guidelines for Prevention of Infective Endocarditis. Issue 6 (January 2013) - Ansari, Julia; Garcha, Gurkaran Singh; Huang, Henry; Bakaeen, Faisal G.; Virani, Salim S.; Jneid, Hani
We describe the case of a 63-year-old man with a known murmur who presented with a 4-month history of intermittent fever and a progressive reduction in energy level after a transrectal prostate biopsy (TRPB). He subsequently presented with acute heart failure secondary to aortic valve cusp rupture caused by endocarditis and underwent urgent aortic valve surgery. The 2008 American College of Cardiology/American Heart Association Guideline update on infective endocarditis has narrowed the use of antibiotic prophylaxis before most accepted dental procedures and continues to recommend against prophylaxis before genitourinary or gastrointestinal procedures. In contrast, the American Urological Association recommends the use of fluoroquinolones for the prevention of transrectal ultrasound–derived infectious complications. Notably, TRPB is associated with a high frequency of bacteremia and bacteriuria. In our case, an antibiotic course before the procedure and a more meticulous medical work-up after febrile illness might have mitigated the patient's catastrophic medical presentation.